Counseling Values ​​in the Thoughts of Ki Hadjar Dewantoro - adiputra, Sofwan; Mujiyati, Mujiyati (Universitas Lampung, 2024)
The application of innovation and creativity in counseling can help in building the relationship process between the client and the counselor. Researchers try to construct a counseling model by placing cultural values, and indigenous studies as the philosophy of the study concept. One approach that meets these elements is the